Beyond intimacy : radical proximity and justice in three Mexican poets - Karageorgou-Bastea, Christina (McGill-Queen's Iberian and Latin American cultures series ;, 2023)
"Karageorgou examines important philosophical and literary questions that ultimately speak about the relationship between art and justice through the substantial works of three contemporary Mexican poets: Poesida (1996) by Abigael Bohorquez (Mexico, 1936-1995), Migraciones (1979-2017) by Gloria Gevirtz (Mexico, 1943-), and Ansina (2015) by Myriam Moscona (Mexico, 1955-). The first was gay, and died of AIDS, the other two are Jewish, and, in the case of Moscona, wrote Ansina using Judeo-Spanish (early modern Spanish written with the Hebrew alphabet). Karageorgou's core argument is that lyric poetry and justice-making are two different forms of social praxis, comparable on the grounds of their aspiration to harmony and their work in constructing and expressing the social space of intimacy."--